Construction of Reality and Social Criticism in the Frame of Online Media (Framing Analysis of News on the Kanjuruhan Football Tragedy in Tempo Online Magazine October 10-16 2022 Edition) - Dela Sulistiyawan Junior (Syntax Corporation Indonesia, 2023)
The rapid development of social media provides easy access to unlimited information and freedom of information. Access to the internet allows every individual to access a variety of available information. Information about the Kanjuruhan football tragedy which caused many fatalities is an interesting topic for the media to cover. The methodology used in this research is framing analysis developed by Pan and Kosicky, while the approach adopted is a qualitative approach. The findings obtained from this investigation are that Tempo online magazine's reporting on the tragedy was critical, informative and very provocative. These indications can be seen from the results of the framing analysis carried out, namely in the framing of the main news: in the Kanjuruhan tragedy there were errors and omissions caused by the security team (either the political committee or police officers), syntactic elements: strengthening the main framing by using unbalanced quotes from sources and the news writer has too many opinions, script elements: strengthening the news, the How element to reduce the why element, thematic elements: there are 5 big themes in the news as material for the news writer, rhetorical elements: the use of cover photos and several graphics and words used to emphasize elements of news that seem hyperbolic and provocative. Furthermore, it can be concluded by researchers that Tempo Online magazine constructs reality for the purposes of social criticism to the Kanjuruhan tragedy competition committee and the government, especially the Indonesian National Police, in reporting through a framing process.